2017
DOI: 10.1007/s00429-017-1383-5
|View full text |Cite
|
Sign up to set email alerts
|

Human astrocytes: structure and functions in the healthy brain

Abstract: Data collected on astrocytes’ physiology in the rodent have placed them as key regulators of synaptic, neuronal, network, and cognitive functions. While these findings proved highly valuable for our awareness and appreciation of non-neuronal cell significance in brain physiology, early structural and phylogenic investigations of human astrocytes hinted at potentially different astrocytic properties. This idea sparked interest to replicate rodent-based studies on human samples, which have revealed an analogous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
226
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(253 citation statements)
references
References 96 publications
5
226
1
3
Order By: Relevance
“…This approach revealed that divergent gradients of cell type-specific gene expression underpin intercardinal axes of the structural manifold, particularly of non-neuronal cell types. Increased glia-to-neuron ratios in transmodal compartments of the structural manifold may support higher order cognitive functions, given comparative evidence showing steep increases in this ratio from worms to rodents to humans [76][77][78][79] . Astrocytes, in particular, exhibit morphological variability that may lend a cellular scaffold to functional complexity and transmodal processing 76 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach revealed that divergent gradients of cell type-specific gene expression underpin intercardinal axes of the structural manifold, particularly of non-neuronal cell types. Increased glia-to-neuron ratios in transmodal compartments of the structural manifold may support higher order cognitive functions, given comparative evidence showing steep increases in this ratio from worms to rodents to humans [76][77][78][79] . Astrocytes, in particular, exhibit morphological variability that may lend a cellular scaffold to functional complexity and transmodal processing 76 .…”
Section: Discussionmentioning
confidence: 99%
“…Increased glia-to-neuron ratios in transmodal compartments of the structural manifold may support higher order cognitive functions, given comparative evidence showing steep increases in this ratio from worms to rodents to humans [76][77][78][79] . Astrocytes, in particular, exhibit morphological variability that may lend a cellular scaffold to functional complexity and transmodal processing 76 . For example, a uniquely human inter-laminar astrocyte was recently discovered with long fibre extensions, likely supporting long-range communication between distributed areas that may contribute to flexible, higher-order cognitive processing 80 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the two studies cannot be directly compared because (a) different K + concentrations ([K + ]) were used in the pipette and bath solutions, which affects resting potentials and (b) the age of the patients analyzed varied greatly (4 months to 14 years vs. mean age of 34 years), which may explain the higher R i of cells in the former study ( R i = 288 MΩ vs. 140 MΩ) (for developmental changes in R i , see Kressin, Kuprijanova, Jabs, Seifert, & Steinhäuser, ). Referring to these two studies, it has been speculated that an apparently higher R i in human versus rodent astrocytes represents an evolutionary adaptation to the larger size of astrocytes, as it results in an increased length constant (Oberheim Bush & Nedergaard, ; Vasile et al, ). However, the whole cell current patterns shown in the papers by Bordey and Sontheimer () and Hinterkeuser et al () indicate that the authors had analyzed NG2 glial cells and not astrocytes.…”
Section: Functional Properties Of Human Astrocytes and Ng2 Gliamentioning
confidence: 99%
“…Morphological studies revealed that astrocytes in the human cortex are larger, more complex and more diverse than those in rodents (Oberheim et al, 2009;Oberheim, Wang, Goldman, & Nedergaard, 2006;Vasile, Dossi, & Rouach, 2017). In addition to fibrous astrocytes in white matter and protoplasmic astrocytes in grey matter, two morphologically distinct subtypes of GFAP-positive cells, interlaminar and varicose projection astrocytes, are exclusively found in the cortex of higher primates (Colombo & Reisin, 2004;Colombo, Yáñez, Puissant, & Lipina, 1995;Oberheim et al, 2009;Sosunov et al, 2014).…”
Section: Astrocytesmentioning
confidence: 99%
“…Increased GP plasma levels have been associated with immunomodulating effects, drug-transporting proteins (e.g., histamine, serotonin), regulation of metabolism, and neuroinflammation (56,57). AGP expression in astrocytes also appears to mediate astrocyte-microglia interactions during neuroinflammation (58,59). In addition, GPs have been investigated as potential biomarkers for depression due to their ability to bind major classes of antidepressant drugs, such as tricyclic antidepressants and selective serotonin reuptake inhibitors (60).…”
Section: Discussionmentioning
confidence: 99%